Designing a Mobile-Based Student Financial Billing Information System at IAI AL-AZIS (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The rapid development of information technology has played a crucial role in modernizing administrative functions within higher education, particularly in addressing inefficiencies in the student financial billing process. Traditionally, this process at many institutions has relied on manual methods, often leading to delays, data entry errors, limited access to real-time information, and a general lack of transparency. Recognizing these challenges, the Islamic Institute of Al-Zaytun Indonesia (IAI AL-AZIS) initiated the development of a mobile-based Student Financial Billing Information System aimed at streamlining access to tuition-related data. This system is designed to provide students with up-to-date information regarding their tuition fees, payment history, and timely billing notifications. To achieve this, the research followed the System Development Life Cycle (SDLC) methodology using the Waterfall model, incorporating data gathered through field observations, interviews with key stakeholders, and a comprehensive literature review. The system architecture was visualized using Data Flow Diagrams (DFD) and Entity Relationship Diagrams (ERD), while the user interface was developed with a mobile-first design approach tailored for Android platforms to ensure ease of access and usability. Key features of the system include modules for retrieving billing statements, monitoring payment history, and receiving alerts for upcoming due dates. Additionally, administrative functionalities such as data entry, payment verification, and automated report generation were integrated to reduce manual workload. Beyond enhancing user experience and operational efficiency, the system also supports interoperability with academic information systems and government reporting tools like Feeder PDDIKTI. As a result, this study provides a practical and adaptable solution for higher education institutions seeking to improve financial service delivery through mobile technology. By aligning digital innovation with institutional needs, the proposed system offers a scalable framework that supports transparency, accountability, and more efficient management of student financial information.